Efficient and secure hybrid chaotic key generation for light encryption device block cipher - Hussain M. Al-Saadi; Imad S. Alshawi (Institute of Advanced Engineering and Science, 2023)
Lightweight cryptographic algorithms must develop to ensure the confidentiality and integrity of the data in resource-constrained devices. Keys are vital to every cryptography algorithm because they provide randomness, complexity, unexpected nature, and robustness. A light encryption device (LED) is considered a lighter version of advanced encryption standard (AES), but it is vulnerable to related key attacks due to using the same key during the whole encryption process. This paper presents a hybrid chaotic key generator (HCKG) based on 3D Lorenz, and 2D Henon maps to generate a highly randomized key that combines with the LED to provide a high level of secure encryption on resource-constrained devices. We modified the HCKG every four rounds via simple operations to get the subkeys and XORed it with the state to increase the complexity of the ciphertext. Moreover, the HCKG with subkeys allows us to decrease the total number of LED rounds from 32 to 24 to minimize the calculation cost while maintaining a high level of security. National Institute of Science and Technology (NIST) test suite proves that the proposed LED-HCKG demonstrates a high-performance increase by nearly 0.3283 higher than LED concerning data integrity and secrecy.